Conflicts in the Middle East since 1945 - Milton-Edwards, Beverley (Making of the contemporary world, 2001)
Since the Second World War, conflicts such as the Iran-Iraq War and the Kuwait Crisis have made the Middle East the main focus of military attention. Conflicts in the Middle East since 1945 analyses the nature of conflict in the Middle East, with its racial, ethnic, political, cultural, religious and economic factors. Giving a much needed historical overview, the main conflicts are also put in their wider contex with a thematic debate of issues, such as: the emergence of radical Islam; the resolution of conflicts; diplomacy and peace-making; the role of superpowers; Conflicts in the Middle East since 1945 offers an authoritative account of the key issues associated with such conflicts as the Arab-Israeli dispute, conflicts in the Lebanon and the unresolved Kurdish issue. The authors also explore the likely future of current conflicts and the problems of conflict resolution in the new millennium.